Etiology and epidemiology of digital dermatitis in Australian dairy herds. - McPherson A; Tranter B; Phipps A; Laven R; House J; Zadoks RN; Rowe S (Elsevier B.V., 2024)
ABSTRACT Bovine digital dermatitis (BDD) is an important cause of lameness in dairy cows worldwide. However, there is very little known about this disease in Australian herds, which are predominantly managed on pasture. The primary objectives of this cross-sectional study were to describe the presence and prevalence of BDD in Australian dairy herds and to characterize the microbiota of healthy skin and M4 lesions of BDD-affected, pasture-managed cows. Cows from 71 dairy herds were examined at milking time to identify the presence of BDD lesions. True prevalence was estimated using Bayesian methods with informative priors for sensitivity and specificity. Biopsy samples (n = 60) were collected from cows with and without BDD-lesions in 7 pasture-based herds. The microbiota in the superficial and deep strata of each tissue biopsy were characterized via sequencing of the V3-V4 region of the bacterial ribosomal RNA gene. Lesions were detected in 1,817 (11.5%) of 15,813 cows, and in 68 of 71 (95.8%) herds. The median herd-level apparent and true prevalences of BDD were 8.5 and 18.1%, respectively, but this varied considerably between farms. On farms with BDD, M4 lesions accounted for 70 to 100% of all lesions (interquartile range = 95.1 to 100%, median = 100%). M2 lesions (i.e., large ulcerative lesions) were observed at low prevalence (<2.2%) in the few herds (7/71, 9.9%) where they were found. There was a statistically significant difference in the composition of the microbiota between healthy skin and M4 lesions but not between superficial and deep tissue layers. Several gut- and effluent-associated bacterial taxa, including Lentimicrobium and Porphyromonas, which have previously been associated with BDD, were abundant in BDD lesions but not in control biopsies. Our study supports the idea that such taxa are involved in, though possibly not essential to, lesion development and persistence in pasture-managed cows in Australia. Our results also suggest that Dichelobacter may contribute to the disease process. We conclude that BDD is likely to occur in most Australian dairy farms, but that further studies are needed to identify its impact on cow welfare and productivity. Further investigation of the etiology of BDD in Australian dairy herds is also necessary to inform prevention and control strategies. INTERPRETIVE SUMMARY: We visited 71 farms in Australia to estimate the prevalence of bovine digital dermatitis (an infectious skin disease that causes lameness in cows). Most farms (68 / 71) were identified to be endemic for the disease, but that the painful lesion types (score = M2) were uncommon. Microbiome analysis was conducted on 60 biopsy sample of cows with and without BDD lesions. We found that cows with BDD had higher abundances of gut- and effluent-associated bacterial taxa, including Lentimicrobium and Porphyromonas. We conclude that BDD is present on most Australian dairy farms.
Keywords: digital dermatitis; lameness; microbiome; true prevalence; Cattle; Animals; Cattle Diseases; Female; Cross-Sectional Studies; Digital Dermatitis; Australia; Dairying; Lameness, Animal; Prevalence